1999
DOI: 10.1090/s0002-9947-99-02544-1
|View full text |Cite
|
Sign up to set email alerts
|

Inverse spectral analysis with partial information on the potential, II. The case of discrete spectrum

Abstract: Abstract. We discuss results where the discrete spectrum (or partial information on the discrete spectrum) and partial information on the potential q of a one-dimensional Schrödinger operator H = − d 2 dx 2 +q determine the potential completely. Included are theorems for finite intervals and for the whole line. In particular, we pose and solve a new type of inverse spectral problem involving fractions of the eigenvalues of H on a finite interval and knowledge of q over a corresponding fraction of the interval.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(158 citation statements)
references
References 32 publications
4
150
0
Order By: Relevance
“…Later, refinements by Hald [17] and Suzuki [34] of Hochstadt and Lieberman's theorem showed that the boundary conditions at x = 1 for L 1 and L 2 need not be assumed a priori to be the same and that if q is continuous, then one only needs λ 1,n = λ 2,m(n) for all values of n but one, that is, one eigenvalue can be missing. However, this is no longer true if the boundary condition at x = 1 is different and q is discontinuous for all values of n but one (see [16]). The same boundary condition for L 1 and L 2 at x = 0, however, is crucial for Hochstadt and Lieberman's theorem to hold (see [33]).…”
Section: Guangsheng Wei and Hong-kun Xumentioning
confidence: 99%
See 1 more Smart Citation
“…Later, refinements by Hald [17] and Suzuki [34] of Hochstadt and Lieberman's theorem showed that the boundary conditions at x = 1 for L 1 and L 2 need not be assumed a priori to be the same and that if q is continuous, then one only needs λ 1,n = λ 2,m(n) for all values of n but one, that is, one eigenvalue can be missing. However, this is no longer true if the boundary condition at x = 1 is different and q is discontinuous for all values of n but one (see [16]). The same boundary condition for L 1 and L 2 at x = 0, however, is crucial for Hochstadt and Lieberman's theorem to hold (see [33]).…”
Section: Guangsheng Wei and Hong-kun Xumentioning
confidence: 99%
“…Several important generalizations of Hochstadt and Lieberman's theorem are given by Gesztesy and Simon [16] who consider the case where the L 1 [0, 1] potential q is known on a larger interval [0, a] with a ∈ [1/2, 1) and assume that the set of common eigenvalues of L 1 and L 2 is sufficiently large. Another result in [16] is to assume that the potential q belongs to C 2k for some k ∈ N 0 near 1/2 so that C 2ksmoothness can replace the knowledge of some (k + 1) eigenvalues, that is, (k + 1) eigenvalues can be missing. In [10], del Rio, Gesztesy and Simon further study the case where a can be any number in the interval (0, 1).…”
Section: Guangsheng Wei and Hong-kun Xumentioning
confidence: 99%
“…In [9,10], Gesztesy, Simon and Malamud gave some new uniqueness results in inverse spectral analysis with partial information on the potential for scalar and matrix Sturm-Liouville equations, respectively. Gesztesy and Simon [9] showed that more information on the potential can compensate for less information on the spectrum. In 2001, Sakhnovich [11] studied the existence of solution to the half inverse problem.…”
Section: Introductionmentioning
confidence: 99%
“…The similar problems with the potential known on the interval (a, π) for arbitrary a ∈ (0, π/2) have been studied in [20,25] and other papers. Our results also can be applied to this case.…”
mentioning
confidence: 99%